IDENTIFICATION OF FISH SPECIES IN THE COASTAL WATERS OF THE KEPENGHULUAN SERUSA, BANGKO SUB DISTRICT, ROKAN HILIR REGENCY, RIAU PROVINCE - Putra, Ridwan Manda; Pulungan, Chaidir P; ', Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The coastal waters of the Kepenghuluan Serusa village was inhabit bynumerous fish species. Information about it, however, is almost none. Tounderstand the type of fish present in that area, a study has been conducted fromMarch to April 2015. The purpose of this research is to identify the fish speciescaught by fishermen in the Kepenghuluan Serusa village. Samplings were donefour times, once a week, using scraping nets (mesh size 1-2 cm) and gillnet (meshsize 1,5-2 inch). The fish sampled were then identified based on Saanin (1968),Kottelat et al, (1993) and Matsuura et al,(2011). Results shown that there were787 fishes captured, consist of 20 fish species and they were belonged to 17genera, 15 families and 8 order. They were Congresox talabon, Setipinna taty,Stolephorus baganensis, Hemipimelodus borneesis, Harpadon nehereus,Hemirhamphus far, Strongylura strongylura, Terapon theraps, Johnius coitor,Panna microdon, Liza parmata, Liza tade, Eleutheronema tetradactylum,Taenioides anguillaris, Trichiurus savala, Cynoglossus cynoglossus, Cynoglossuslingua, Cynoglossus microlepis, Zebrias zebra and Gastrophysus oblongus. Themost common species was Eleutheronema tetradactylum (211 fishes) and Pannamicrodon (132) and Stolephorus baganensis (124).Keyword: Fish identification, Coastal waters, Serusa.